Predicting oral health behaviors among Iranian students by using health belief model - Azam Goodarzi; Alireza Heidarnia; Sedigheh Sadat Tavafian; Mohammad Eslami (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: The aim of this study is assessing predictors to oral health behavior in Iranian students based on the health belief model. MATERIALS AND METHODS: This cross-sectional study was conducted on 416 (applying the statistical estimation) of fifth-grade female students of Tehran in 2016. Random cluster sampling method was used to recruit students. The inclusion criteria were being grade five female student (aged 10-12 years), and studying in governmental schools, and having a signed consent from the child's parent or legal guardian. Logistic regression analysis was used to identify the variables that predict oral health behaviors. RESULTS: Overall, 416 female students were entered into the study. Of these, only 55.3% of the students reported that they were brushing at least twice a day, 22.4% were using dental floss at least once a day, and 23.1% reported checking their teeth every 6 months. The results obtained from the logistic regression analysis indicated that perceived self-efficacy, was the significant predicting factor for brushing at least twice a day (odds ratio [OR] = 1.34, 95% confidence interval [CI] =1.06-1.69, P = 0.012) and use of dental floss at least once a day (OR = 1.61, 95% CI = 1.14-2.27, P = 0.007). Furthermore, mother's job predicted use of dental floss at least once a day by (OR = 1.83, 95% CI 1.07-3.10). Perceived benefits were the significant predicting factor for 6 months check (OR = 1.78, 95% CI = 1.14-2.77). CONCLUSION: The current study provides evidence oral health can be promoted by increasing perceived self-efficacy and enhancing perceived benefits in female students.